Suppression potential of selected vermicomposts against root-knot nematode (Meloidogyne incognita) under in vitro, pot, and field conditions - Gebrehana, Zerihun Getachew; Gebremikael, Mesfin T.; Beyene, Sheleme; Wesemael, Wim M. L.; De Neve, Stefaan (Frontiers in Plant Science, 2025)
The root-knot nematode Meloidogyne incognita presents a serious threat to high-value crops in tropical and subtropical regions, particularly in Ethiopia, causing substantial yield and quality losses. Vermicompost, whether applied in solid form or as an extract, has shown promise in managing root-knot nematodes (RKNs). However, its effectiveness is influenced by factors such as the quality and type of vermicompost, the application rate, and the composition of parasitic nematode communities in the soil. This study utilized selected vermicomposts at varying rates in in vitro, pot, and field experiments to evaluate their potential for suppressing M. incognita and their effects on the growth and yield of tomato and hot pepper. The in vitro experiments demonstrated that all vermicompost extracts exhibited toxicity to J2. In particular, VC10 and VC11 showed higher efficacy, resulting in 55% and 78% mortality of J2 after 24 and 72 h of exposure, respectively, compared to the control and VC12. The interaction between vermicompost type, application rate, and nematode density significantly influenced tomato growth and nematode parameters in the pot experiment. The application of VC10 and VC11 at high doses (10 and 20 t ha−1) and low nematode density (50 J2) increased root fresh weight while reducing galls and nematode populations in tomato roots. Conversely, VC12 at a high application rate (20 t ha−1) and high nematode density (500 J2) led to an increase in root galls and nematode populations, suggesting a preference for RKNs rather than the expected nematicidal effect. The study indicates that the suppressive effect of vermicompost on nematodes varies with nematode density, depending on the type and amount of vermicompost used. Field experiments revealed that vermicompost amendments not only suppressed posttreatment nematode populations but also significantly improved hot pepper yield. Particularly, VC10 applied at high rates (10 and 20 t ha−1) resulted in lower nematode densities and higher marketable fruit yield compared to other vermicompost treatments and the conventional treatments (control, farmer practice, and recommended fertilizer). This highlights the long-term benefits of vermicompost application for nematode management and soil health. In addition, vermicompost amendments improved soil chemical properties. Overall, vermicompost offers greater benefits than farmers’ practices and high-cost chemical fertilizers for soil improvement, while also enhancing tomato and hot pepper yields in nematode-infested smallholder farms.